Apodiktilise seadusesõna algupärast - Annus, Amar (Usuteaduslik Ajakiri, 2003)
Amar Annus, On the Origin of the Apodictic Law. The basic distinction between the apodictic and casuistic forms of law in the Hebrew Bible was first introduced by A. Alt. The apodictic commandment was a part of the covenant between Yahweh and Israel, and therefore a part of the Temple liturgy. The casuistic form of the law of Israel was probably inherited from the Mesopotamian traditions, where the casuistic form was the format for all kinds of sciences. While the casuistic part of Israelite law finds its forerunner in Mesopotamian science, the apodictic form ultimately derives its origin from the vassal treaties and the service manuals (Dienstanweisungen) as they have survived from the Hittite and Neo-Assyrian sources.